The Novel Inodilator ORM-3819 Relaxes Isolated Porcine Coronary Arteries: Role of Voltage-Gated Potassium Channel Activation. Issue 3 (September 2019) - Márton, Zoltán; Pataricza, János; Pollesello, Piero; Varró, András; Papp, Julius Gy.
Abstract : Abstract: Relaxation and changes in the transmembrane potential of vascular smooth muscle induced by ORM-3819, a novel inodilating compound, were investigated in isolated porcine coronary arteries. Isometric tone was studied on arterial rings precontracted by KCl (30 mM), and resting membrane potential was investigated by a conventional microelectrode technique. ORM-3819 in the concentration range 0.38–230.6 µM evoked concentration-dependent relaxation with a maximum value of 58.1% and an effective concentration of the relaxing substance that caused 50% of maximum relaxation of 72.2 µM. The maximum hyperpolarization produced by ORM-3819 at a concentration of 120 µM (−2.6 ± 0.81 mV, N = 10) did not differ significantly from that induced by C-type natriuretic peptide (CNP), an endogenous hyperpolarizing mediator, at a concentration of 1.4 µM (−3.6 ± 0.38 mV, N = 17). The same effect elicited by the known inodilator levosimendan was less pronounced at a concentration of 3.7 µM: −1.82 ± 0.44 mV, N = 22 ( P < 0.05 vs. CNP). The voltage-gated potassium channel inhibitor 4-aminopyridine, at a concentration of 5 mM, attenuated the relaxation induced by ORM-3819 at concentrations of 41.6 or 117.2 µM. These results suggest that ORM-3819 is a potent vasodilating agent able to relieve coronary artery vasospasm by causing hyperpolarization of vascular smooth muscle cells through processes involving activation of voltage-gated potassium channels.